The Effect of Using a Rocker Arm on the Performance and Efficiency of a 200cc 4 Stroke Motor - Afif Fakhruddin; A'rasy Fahruddin (Universitas Muhammadiyah Sidoarjo, 2021)
In Indonesia, many people often use two-wheeled vehicles compared to four-wheeled vehicles, and so many people want the best speed and performance of their motorbikes compared to the manufacturer's standards. Modifying the camshaft or what is more familiarly known as